The prospects for vaccines against HIV-1: more than a field of long-term nonprogression? - Sheppard, N; Sattentau, Q (2005)
More than 20 years have passed since the human immunodeficiency virus (HIV)-1 was identified as the cause of AIDS (acquired immune deficiency syndrome). With rapid early progress, the development of a vaccine was predicted within 2-10 years. However, over two decades later, we have seen only a single vaccine candidate complete Phase III clinical efficacy trials. These trials showed the vaccine was not able to protect the trial volunteers from HIV infection or subsequently modify the early clinical progression. It is now accepted that the initial optimism in the field was misguided, as the complexity of the problem stretched beyond the known horizons of vaccinology, immunology and retrovirology. In the intervening 20 years, unprecedented research efforts have pushed the cutting edge of these fields forward to such a degree that we are better able to put the problem of developing a vaccine for HIV-1 into context. Now it is time to examine the prospects for HIV-1 vaccines and ascertain whether real progress is being made.